A case of periampullary adenocarcinoma in neurofibromatosis type 1 - Kistler, C. Andrew; Johnson, Jennifer M.; Winter, Jordan M.; Baliff, Jeffrey P.; Siddiqui, Ali A.; Sama, Ashwin R. (Journal of Gastrointestinal Oncology; Vol 5, No 6 (December 20, 2014): Journal of Gastrointestinal Oncology, 2014)
Neurofibromatosis type 1 (NF-1) is an autosomal dominant genetic disorder with a known predisposition to gastrointestinal neoplasms such as stromal tumors and carcinoids. Adenocarcinomas (ACs) of the gastrointestinal tract are relatively rare in patients with NF-1, especially those found in the periampullary region. We present a case report of periampullary adenocarcinoma in a 56-year-old woman with NF-1 who presented with abdominal pain and obstructive jaundice.